Accessibility of Medicines for Children: A Systematic Review - Chen, Zhe; Li, Siyu; Zeng, Linan; Liu, Yan; Zhang, Miao; Choonara, Imti; Zhang, Lingli (Frontiers in Pharmacology, 2021)
Background: Accessibility of medicines for children is a matter of global concern. Medicines prescribed for children are often off-label. To formulate appropriate policies and undertake necessary interventions to improve access to medicines for children, it is necessary to evaluate the accessibility of medicines for children. However, there is no systematic review of the medicine accessibility for children. Methods: Relevant studies were identified through searching Pubmed, Embase, CNKI, Wanfang, VIP, World Health Organization website, and Health Action International website. Besides, the references of included studies as a supplementary search were read. We extracted the basic information of articles (the first author, published year, the name of journal, research institution, etc.), the basic study characteristics (survey area, survey time, survey method, survey medicine lists, the number of medicine outlets surveyed, etc.), and the study results (the current situation of the accessibility of medicines for children, including the availability, price, and affordability of medicines for children, etc.). Two reviewers independently selected studies and extracted the data. Descriptive analysis methods to analyze the current situation of the accessibility of children's medicines were used. Results: A total of 18 multicenter cross-sectional studies were included in this systematic review, which were from low-income and middle-income countries. 17 studies (17/18, 94.4%) used the WHO/Health Action International (HAI) medicine price methodology to investigate the accessibility of medicines for children. 15 studies (15/18, 83.3%) were selected to investigate medicines based on the WHO Model List of Essential Medicines for Children (WHO EMLc). In the public sectors, the availability of originator brands (OBs) ranged from 0 % to 52.0 %, with a median of 24.2 %, and the availability of lowest-priced generics (LPGs) ranged from 17.0 % to 72.6 %, with a median of 38.1 %. In the private sectors, the availability of OBs ranged from 8.9 % to 80 %, with a median of 21.2 %. Conclusions: The availability of medicines for children in both public sectors and private sectors in low-income and middle-income countries is low. The MPR of OBs is higher than that of LPGs, and the LPGs is implicated with the better affordability.